Pharmacokinetic Variability of Amikacin After Once-Daily and Twice-Daily Dosing Regimen in Full-Term Neonates - Katarina Vučićević; Zorica Rakonjac; Branislava Miljković; Borisav Janković; Milica Prostran (Elsevier, 2014)
The purpose of the study was to compare peak (Cpeak) and trough (Ctrough) amikacin levels after twice-daily (TD) or once-daily dosing (OD) in full-term neonates. Additionally, the study aimed to address amikacin pharmacokinetics and its variability. Data included 31 patients born on term. Amikacin daily dose was 15 or 20 mg/kg depending on the neonate's age. Patients randomly received amikacin every 12 or 24 h. In all patients corresponding Cpeak and Ctrough were taken. Volume of distribution (Vd), clearance (CL) and half-life (t1/2) were calculated. Mean Cpeak of 21.79 μg/ml in the TD group was statistically different from Cpeak of 36.39 μg/ml in the OD group. Average Ctrough in TD (5.67 μg/ml) was statistically different from the corresponding 3.99 μg/ml in the OD group. Mean amikacin Vd, CL, and t1/2 were 0.78 ± 0.38 l/kg, 86.99 ± 48.22 ml/h∙kg, and 6.81 ± 2.51 h, respectively. High interindividual pharmacokinetic variability was observed. Further analysis showed that neonatal age contributed to the pharmacokinetic parameters' values. Statistically significant difference in CL and t1/2 was observed between patients age ≤ 2 and > 2 days on therapy initiation. As expected, amikacin given OD achieved higher Cpeak and lower Ctrough than TD. Based on the results, observed variability in amikacin pharmacokinetics was possibly due to the renal maturation process. Keywords:: amikacin, pharmacokinetics, full-term neonate, dosing regimen